The dilema of Bantu church music - Basil, Brother (International Library of African Music, 1957)
It is true that adaptations of old, and not so old, folk tunes to hymns are often forward as a possible solution to restore African church music. But I agree with Canon E.E. Lury and Father K. Carroll who show that the general attitude of Africans towards their own music in Church is negative. Several writers in this journal and elsewhere also expressed convergent views: old and young are adamant on this point. The old, beside their ingrained conservatism, deeper still in the African at large, shall howl their chant as long as they live, on the strength of “the virtue that is given it by usage and association.” Appreciated from a Christian point of view, this attitude is to be respected, for the pitfall is not far away: native folklore does not lend itself for a long time to musical adaptations to church service, and if one is not informed, one might invite the faithful to pray to-day on the themes which only yesterday called them to dance. The younger generation, though it is eager to get out of the cangue of the past, is also opposed to its own music in church, but for a motive of its own. “Inferior music” says of his own the young sophisticated African. “Savage music!” does he label his neighbour’s.
Keywords: African Music